High open-circuit voltage in lead sulfide quantum dot solar cells via solution-phase ligand exchange with low electron affinity cadmium halides - Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Mitra, Anurag; Rath, Arup K. (JOURNAL OF MATERIALS CHEMISTRY A, 2023)
The deployment of colloidal quantum dots (QDs) in building high-performance solar cells and other optoelectronic applications relies on the passivation of unsaturated surface atoms through ligand engineering to attain a trap-free energy bandgap and strong QD coupling while maintaining the quantum confinement effect. Despite major advancements in surface passivation strategies, the open circuit voltage (V-oc) of lead sulfide (PbS) QD solar cells is limited by undesirable sub-bandgap states and high-bandtail states. The most advanced solution-phase ligand exchange strategy for PbS QDs depends on lead halide ligands, which improved the photocurrent and fill factor in QD solar cells significantly, but only an incremental change in V-oc is observed. Here we showcase a solution-phase hybrid ligand passivation strategy for PbS QDs using shallow electron affinity cadmium halide and thiol ligands. The cadmium halide ligand treatment results in the sub-monolayer substitution of surface Pb atoms by Cd atoms. The photophysical properties of QDs improve significantly to show intense band edge emission, diminished trap emission and reduced Urbach tail states. The photovoltaic devices built using cadmium halide-treated QDs show low reverse saturation current, which helps to attain a record 0.7 V V-oc (for a 1.28 eV bandgap) and 12.3% PCE.

Multi-bandgap quantum dots ensemble for near-infrared photovoltaics - Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Rath, Arup K. (Energy Technology, 2023)
Narrow bandgap quantum dots (QDs) are an important class of materials for near-infrared (NIR) optoelectronic devices owing to their size-tunable bandgap and chemical root processing. In photovoltaic applications, NIR QDs could be particularly useful to complement the sub-bandgap transmission loss of NIR solar radiation from perovskite and c-Si solar cells. However, insufficient carrier extraction thickness associated with the narrow NIR excitonic bandwidth of QDs limits the conversion efficacy of the broad NIR solar spectrum. Here, we utilize a multi-bandgap QD ensemble which widens the NIR absorption bandwidth to mimic the broad solar spectrum. A solution-phase ligand passivation strategy is used to control doping properties and energy level alignment of multi-bandgap QDs. We successfully developed bulk-heterojunction solar cells using the multi-bandgap QD ensemble, which yields higher carrier extraction thickness and broader NIR absorption. The gain from NIR absorption and carrier transport resulted in higher short-circuit current generation and power conversion efficiency (PCE) in solar cell devices. The champion device shows 8.73% PCE under 1.5 AM solar illumination and 7.44% and 5.05% PCE for the NIR photons transmitted from perovskite and c-Si layers.
Keywords: bulk-heterojunctions; multi-bandgap; near-infrared; quantum dots; solar cells; surface passivation

Organic field effect transistors comprising copolymers synthesized without structure-directing moieties with enhanced carrier mobility - Swain, Gitanjali; Javaregowda, Bharathkumar H.; Dambhare, Neha V.; Krishnamoorthy, Kothandam (ACS Applied Electronic Materials, 2023)
Conjugated materials are synthesized by C-C bond formation reactions. Trimethyltin and boronic acid are two widely used structure-directing moieties. While using the ethynyl moiety as a part of the monomer, additional structure-directing moieties are not needed. However, ethynylene will be part of the conjugated material. Often, the polymers with an ethynylene moiety negatively impact the polymers' properties. However, the ethynylene moiety could minimize the dihedral angle if the monomer has steric functionalities. For example, BODIPY is an attractive monomer due to its high molar extinction coefficient, partial quinoidal character, and high quantum yield. However, materials based on BODIPY exhibited poor charge carrier mobility due to steric hindrance generated by four methyl groups. Herein, we copolymerize BODIPY with ethynylene comprising i-indigo and thieno-i-indigo. The copolymer with thieno-i-indigo showed increased molecular weight and significantly reduced band gap compared to the copolymer with i-indigo. The copolymer with i-indigo showed immeasurably low hole transport mobility. On the other hand, the copolymer with thieno-i-indigo exhibited 0.003 cm2V(-1) s(-1). These measurements were made using field effect transistors. We also measured the charge carrier mobility using the space charge-limited current method. Both copolymers exhibited a mobility of 10(-3) cm(2) V-1 s(-1).
Keywords: acetylene linkage; BODIPY; field effect transistor; iso-indigo; Sonogashira coupling; thienoisoindigo

Photogating induced high sensitivity and speed from heterostructure of few-layer MoS2 and reduced graphene oxide-based photodetector - Das, Chayan; Kumar, Ashok; Kumar, Suresh; Dambhare, Neha V.; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2023)
Over the past few years, two-dimensional transition metal dichalcogenides (2D-TMDC) have attracted huge attention due to their high mobility, high absorbance, and high performance in generating excitons (electron and hole pairs). Especially, 2D molybdenum disulfide (MoS2) has been extensively used in optoelectronic and photovoltaic applications. Due to the low photo-to-dark current ratio (I-photo/dark) and low speed, pristine MoS2-based devices are unsuitable for these applications. So, they need some improvements, i.e., by adding layers or decorating with materials of complementary majority charges. In this work, we decorated pristine MoS2 with reduced graphene oxide (rGO) and got improved dark current, I-photo/dark, and response time. When we compared the performance of pristine MoS2 based device and rGO decorated MoS2 based device, the rGO/MoS2-based device showed an improved performance of responsivity of 3.36 A W-1, along with an I-photo/dark of about 154. The heterojunction device exhibited a detectivity of 4.75 x 10(12) Jones, along with a very low response time of 0.184 ms. The stability is also outstanding having the same device performance even after six months.

Ultra-fast electro-reduction and activation of graphene for high energy density wearable supercapacitor asymmetrically designed with MXene - Karim, Golam Masud; Dutta, Pronoy; Majumdar, Abhisek; Patra, Amalika; Deb, Sujit Kumar; Das, Snehasish; Dambhare, Neha V.; Rath, Arup K.; Maiti, Uday Narayan (Carbon, 2023)
Controlled perforation of graphene is vital to surpass the performance of supercapacitors that rely on their pristine form. However, their practical utilization has been halted by energy-inefficient and lengthy processing. Here, we are reporting a pulse Joule heating strategy for on-site reduction and activation to realize a multimodal porous framework made of perforated graphene using millisecond current pulses. The multimodal porosity and surface functionalities of graphene were regulated at an ultrafast rate by passing a transient current. Asdeveloped ready-to-use electrode composed of nano-to-macro multimodal porosity displays high areal capacitance of 380.2 mF cm-2 in symmetric two-electrode configuration, which is nearly 1.6 times higher than the nonelectro activated counterpart. Furthermore, a high-performance wearable asymmetric supercapacitor with an areal energy density of 107.8 mu Wh cm-2 was realized using this multimodal porous graphene in combination with suitable negative electrodes made of MXene. High energy density, together with stable and repeatable performance of the wearable device for 10000 cycles of charge-discharge and 5000 cycles of bending, signifies the importance of the as-developed device for practical wearable applications. Direct, simple processing of electrodes and orders of magnitude lower cost-and-processing-time can make the process appealing for practical wearable and other energy storage applications.
Keywords: asymmetric supercapacitor; Graphene activation; Joule heating; Solid-state supercapacitor; Wearable device

High-performance photodetector from p-n junction of vertically aligned SnS2 and reduced graphene oxide - Das, Chayan; Kumar, Suresh; Dambhare, Neha V.; Kumar, Mahesh; Rath, Arup K.; Sahu, Satyajit (ACS Applied Electronic Materials, 2024)
Semiconducting 2D transition metal dichalcogenides (TMDC) became very popular in photodetection due to their high mobility and high rate of generating electron and hole pairs. Over the past decade, MoS2 and WS2 became the most popular TMDC for several applications. On the other hand, due to the complex synthesis process compared to MoS2 and WS2, SnS2 became a less popular 2D material for photodetection. We synthesized vertically aligned SnS2 flakes by a chemical vapor deposition (CVD) process with three temperature zones with controlled argon (Ar) gas flow. Pristine SnS2-based devices are not very suitable for photodetection applications because of their low photo-to-dark current ratio (I ph /I (dark) ), high response time, and low stability. So, they need to be decorated with oppositely doped materials. We decorated pristine SnS2-based devices with rGO nanoparticles, which significantly increased the device's performance. We found a high responsivity (R) of 1.33 A/W, detectivity (D) of 6.95 x 10(11) Jones, I ph /I dark of 102, and a rise time of 0.241 ms (fall time of 1.318 ms) with the rGO decorated SnS2-based device.
Keywords: 2D-SnS2; CVD; p-njunction; photodetector; rGO

Lead-free low-dimensional tetraalkylammonium manganese- and copper-based hybrid organic–inorganic perovskites for visual fluorometric Pb2+ ion detection - Kour, Prachi; Sahu, Pragati; Dambhare, Neha V.; Rath, Arup Kumar; Mukherjee, Shatabdi Porel (ACS Applied Optical Materials, 2024)
For the first time, we have synthesized lead (Pb)-free manganese (Mn)- and copper (Cu)-based hybrid organic–inorganic perovskite (HOIP) compounds, compound 1, (TEA)2MnBr4, compound 2, (TBA)2MnBr4, compound 3, (TEA)2CuBr4, and compound 4, (TBA)CuBr2 (where TEA is tetraethylammonium and TBA is tetrabutylammonium), under ambient conditions via mechanochemical synthesis methodology using a Kakuhunter-made planetary mixer. The compounds are characterized as 2D except for (TBA)CuBr2, which has crystallized in the 0D lattice. The synthesized compounds are phase pure and show a stable solid-state emission at room temperature. The Mn-based perovskite compound 1 showed excellent environmental photostability for over a month and reasonable stability under a relative humidity of 70–80%. The nanoparticle (NP) dispersions of compounds 1 and 2 were used further for fluorescence titration studies using various heavy metal cations, including transition metals and lanthanides (e.g., Y3+, Nb3+, Co2+, Ni2+, Ag+, Zn2+, Cd2+, Pb2+, Gd3+, and Dy3+), where they showed good fluorescence switching by the Pb2+ ion. Compound 1 demonstrated excellent fluorescence switching performance with Pb2+ titration with a Pb2+ detection limit of 2.43 × 10–8 M and hence can be used to fabricate a Pb2+ calorimetric sensor. A preliminary visual thin film-based sensor using NPs of compound 1 was fabricated to test the change in emission from blue to green in correlation with the results obtained in the NP solution during Pb2+ ion sensing. A fascinating in situ ion-exchange-based mechanism for the sensitivity of NPs of compound 1 is confirmed. This study reveals the ability of Pb-free Mn-based HOIPs to detect an oxidizing metal cation, Pb2+, efficiently and quantitatively.

Magnetic chemiresistive Fe-doped In2O3 nanocubes to Tunably detect NO2 at ppm to ppb concentrations - Rudra, Pratyasha; Dambhare, Neha V.; Srihari, Velaga; Das, Sagnik; Rath, Arup Kumar; Saha, Debdulal; Mondal, Swastik (ACS APPLIED NANO MATERIALS, 2024)
Keywords: GAS-SENSING PROPERTIES; METAL-OXIDE NANOSTRUCTURES

Synthesis and processing strategy for high-bandgap PbS quantum dots: a promising candidate for harvesting high-energy photons in solar cells - Shinde, Dipak Dattatray; Sharma, Anjali; Dambhare, Neha V.; Mahajan, Chandan; Biswas, Arindam; Mitra, Anurag; Rath, Arup K. (ACS Applied Materials & Interfaces, 2024)
The wide tunability of the energy bandgap of colloidal lead sulfide (PbS) quantum dots (QDs) has uniquely positioned them for the development of single junction and tandem solar cells. While there have been substantial advancements in moderate and narrow bandgap PbS QDs-ideal for single junction solar cells and the bottom cell in tandem solar cells, respectively; progress has been limited in high-bandgap PbS QDs that are ideally suited for the formation of the top cell in tandem solar cells. The development of appropriate high bandgap PbS QDs would be a major advancement toward realizing efficient all-QD tandem solar cells utilizing different sizes of PbS QDs. Here, we report a comprehensive approach encompassing synthetic strategy, ligand engineering, and hole transport layer (HTL) modification to implement high-bandgap PbS QDs into solar cell devices. We achieved a greater degree of size homogeneity in high-bandgap PbS QDs through the use of a growth retarding agent and a partial passivation strategy. By adjusting the ligand polarity, we successfully grow HTL over the QD film to fabricate solar cells. With the aid of an interface modifying layer, we incorporated an organic HTL for the realization of high-performance solar cells. These solar cells exhibited an impressive open-circuit voltage of 0.824 V and a power conversion efficiency of 10.7%, marking a 360% improvement over previous results.
Keywords: charge transport; lead sulfide; ligand passivation; quantum dots; solar cell

Air-stable double halide perovskite Cs2CuBiBr6: synthesis and memristor application - Betal, Atanu; Chetia, Anupam; Saikia, Dibyajyoti; Karmakar, Krishnendu; Bera, Ganesh; Dambhare, Neha V.; Rath, Arup K.; Sahu, Satyajit (Physical Chemistry Chemical Physics, 2025)
The excellent optical and electronic properties of halide perovskite materials have attracted researchers to investigate this particular field. However, the instability in ambient conditions and toxicity of materials like lead have given some setbacks to commercial use. To overcome these issues, perovskite-inspired materials with less toxic and excellent air-stable materials are being studied. Double perovskite materials are one of the perovskite materials. In this study, we have synthesized air-stable double perovskite Cs2CuBiBr6 using a solution process approach. The characterization of the material revealed that it has excellent crystallinity and high stability. The material shows excellent optical and electronic properties. It can be used in resistive memory devices. It shows stable current-voltage characteristics and analog switching. The ion migration through the active layer and accumulation of charge near the electrode region are the reasons behind the resistive switching.

Fermi-level equilibrium-driven trap filling in multibandgap PbS quantum dot solids enabling record voltage generation and improved carrier transport in high-performance solar cells - Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup Kumar (ACS Energy Letters, 2025)
To leverage the unique optical properties of quantum dots (QDs) in solar cells, it is crucial to address electronic traps from unsaturated surface states of high surface area QDs. Despite advancements in surface passivation, even the best-coupled QD solids exhibit significant sub-bandgap trap states. This study introduces engineered multibandgap PbS QD solids that achieve passivation of deep traps below the conduction band through electron migration from dopant QDs. Our findings indicate that electron flow, driven by Fermi energy balancing in blend films, fills deep trap states, reducing trap density by half and shifting trap energy positions closer to the conduction band. During electrical transport, trap filling minimizes trapping and detrapping events, enhancing overall carrier mobility, despite higher-bandgap dopant QDs not contributing to carrier transport due to their unfavorable energy positions. Improved trap passivation in coupled QD solids leads to a record V oc of 725 +/- 10 meV for the 1.33 eV excitonic peak of QDs and a power conversion efficiency exceeding 14% in solar cells.

Synergistic improvement of narrow bandgap PbS quantum dot solar cells through surface ligand engineering, near-infrared spectral matching, and enhanced electrode transparency - Sharma, Anjali; Shinde, Dipak Dattatray; Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Mitra, Anurag; Girade, Vrushali S.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2025)
The tunability of the energy bandgap in the near-infrared (NIR) range uniquely positions colloidal lead sulfide (PbS) quantum dots (QDs) as a versatile material to enhance the performance of existing perovskite and silicon solar cells in tandem architectures. The desired narrow bandgap (NBG) PbS QDs exhibit polar (111) and nonpolar (100) terminal facets, making effective surface passivation through ligand engineering highly challenging. Despite recent breakthroughs in surface ligand engineering, NBG PbS QDs suffer from uncontrolled agglomeration in solid films, leading to increased energy disorder and trap formation. The limited NIR transparency of commonly used indium-doped tin oxide (ITO) electrodes and inadequate NIR radiation from commercially available solar simulators further compromise the true performance of NBG PbS QDs in solar cells. Here, we employ a hybrid ligand strategy based on inorganic cadmium halide and organic thiol molecules, leading to the partial substitution of surface Pb atoms with Cd heteroatoms. This hybrid ligand strategy substantially reduces undesired QD fusion in solid films, improving the photophysical and electronic properties. By modulating the thickness of the ITO layer and managing refraction loss through a ZnO layer coating, we improved NIR transparency to above 80%. We combine an NIR light source with a solar simulator to achieve near-ideal spectral matching for a broader range with standard AM1.5G illumination. Enhancements in surface passivation of QDs, improvements in NIR transparency of electrodes, and a spectral matched light source setup help us achieve solar cell power conversion efficiencies of 12.4%, 4.48%, and 1.37% under AM 1.5G, perovskite filter, and silicon filter illuminations, respectively. A record open-circuit voltage (V oc) of 0.54 V and short-circuit current density (J sc) of 38.5 mA/cm2 are achieved under AM 1.5G illumination. We attribute these advancements in photovoltaic parameters to the reduction in Urbach tail states and intermediate trap density originating from superior surface passivation of QDs.
Keywords: lead sulfide; ligand passivation; near-infrared; quantum dots; solar cell; tandem solarcell